Faulkner : Myth and Motion - Adams, Richard P. (Richard Perrill), 1917-1977 (Book collections on Project MUSE., 1968)
Faulkner said that "Life is motion" and that "The aim of every artist is to arrest motion, which is life, by artificial means and hold it fixed so that a hundred years later, when a stranger looks at it, it moves again since it is life." The author's purpose is, in the light of these statements, to define Faulkner's intentions as a novelist and to analyze the more important technical devices used to carry them out. Because the poems and prose sketches Faulkner wrote before Soldiers' Pay contain many clues that help to explain what he did in his later and more artistically successful fiction, they are treated more thoroughly than usual. Professor Adams considers the functional relation of the intentions, structures, and texture of Faulkner's work, and shows how the style, imagery, and symbolism support the strategy of making the motion of life visible by stopping it. Originally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905